Boosting CO2 reduction on Fe-N-C with sulfur incorporation: Synergistic electronic and structural engineering. (February 2020) - Pan, Fuping; Li, Boyang; Sarnello, Erik; Hwang, Sooyeon; Gang, Yang; Feng, Xuhui; Xiang, Xianmei; Adli, Nadia Mohd; Li, Tao; Su, Dong; Wu, Gang; Wang, Guofeng; et al.
Abstract: Developing earth-abundant efficient catalysts for CO2 reduction reaction (CO2 RR) is of paramount importance for electrochemical conversion of CO2 into value-added products. Despite numerous studies on iron and nitrogen codoped carbon (Fe-N-C) catalysts, grand challenges exist due to limited performance and understanding of catalytic mechanisms. This study reports a general strategy to boost electrocatalytic CO2 RR activity of Fe-N-C with the incorporation of S atoms to engineer carbon support structure and electronic properties of active Fe–N sites simultaneously via a copolymer-assisted synthetic approach. The employment of N, S comonomers significantly increases the numbers of micropores and surface area, enabling dense atomic Fe–N and enhanced utilization efficiency. The first-principles calculations reveal that S modulation upraises the Fermi energy of Fe 3d and increases charge density on Fe atoms of Fe–N4, thereby enhancing intrinsic catalytic reactivity and selectivity for CO2 reduction by strengthening the binding interaction between the Fe site and key COOH* intermediate. These integrated structural and electronic merits endow Fe-NS-C with outstanding activity (e.g., CO Faradaic efficiency of 98% at an overpotential of 490 mV) and stability (without deactivation in 30 h), ranking it one of the most active Fe-N-C reported to date. The finding offers an innovative design strategy to enable the design of advanced catalysts for CO2 conversion. Graphical abstract: Sulfur addition promotes electrocatalytic CO2 reduction on Fe-N-C by synergistically tailoring structure of carbon support and electronic properties of single atomic Fe–N sites, achieving top-level performance for CO generation among Fe-N-C catalysts. Image 1 Highlights: Sulfur engineering promotes electrocatalytic CO2 reduction on Fe-N-C. Sulfur addition improves numbers and utilization efficiency of atomic Fe-N4 by increasing micropores and surface area. Electron donation from sulfur enhances intrinsic reactivity of Fe-N4 by strengthening binding interaction with COOH*. The integrated structural and electronic benefits yield top-level CO2 RR activity among Fe–N–C catalysts.